Sofosbuvir-Based Regimens in HIV/HCV Coinfected Patients After Liver Transplantation: Results From the ANRS CO23 CUPILT Study. Issue 1 (January 2018) - Antonini, Teresa Maria; Coilly, Audrey; Rossignol, Emilie; Fougerou-Leurent, Claire; Dumortier, Jérôme; Leroy, Vincent; Veislinger, Aurélie; Radenne, Sylvie; Botta-Fridlund, Danielle; Durand, François; Houssel-Debry, Pauline; Kamar, Nassim; et al.
Abstract : Background: A recurrence of hepatitis C virus (HCV) after liver transplantation affects survival in human immunodeficiency virus (HIV)/HCV coinfected patients. This study assessed the efficacy and safety of sofosbuvir (SOF)-based regimens in HIV/HCV coinfected patients after liver transplantation. Methods: Twenty-nine HIV/HCV coinfected transplanted patients receiving tacrolimus-, cyclosporine-, or everolimus-based immunosuppressive therapy were enrolled in the Compassionate Use of Protease Inhibitors in Viral C Liver Transplantation cohort. Their antiviral treatment combined SOF, daclatasvir with or without ribavirin (n = 10/n = 6), or SOF, ledipasvir with or without ribavirin (n = 2/n = 11). Results: The median delay between liver transplantation and treatment initiation was 37.5 months (interquartile range [IQR], 14.4-99.2). The breakdown of HCV genotypes was G1, 22 patients (75.9%); G3, 3 patients (10.3%); and G4, 4 patients (13.8%). The treatment indications were HCV recurrence (≥ F1 n = 23) or fibrosing cholestatic hepatitis (n = 6). Before starting SOF, the HCV viral load and CD4 count were 6.7 log10 IU/mL (IQR, 5.9-7.2) and 342 cells/mm 3 (IQR, 172-483), respectively. At week 4, the HCV viral load was less than 15 IU/mL in 12 (42.9%) patients. The overall sustained virological response 12 was 96.6%. No significant drug-drug interactions were observed. Conclusions: SOF-based treatment regimens produced excellent results in HIV/HCV coinfected patients after liver transplantation, suggesting an important change in their prognosis. Abstract : This multicenter study reports excellent results achieved with interferon-free sofosbuvir-based therapy in hepatitis C-HIV coinfected patients with recurrent hepatitis C, not different from those obtained by monoinfected recipients.